Від героїчного турецького народного оповідання до панегіричних оповідань меддах - Умай Гюнай (Народна творчість та етнографія, 2010)
This article is a comparison of social values and the understanding of ethics in the minstrel stories that have been formed in the historical period of the 15th and the 16th centuries with the Istanbul centred eulogist/meddah stories which have been though to emerged with its classical form in the 18th century. When we look upon the common characters and the scenarios in the Folk Theatre/Orta Oyunu, Karagoz and Eulogist/Meddah Stories at the decline period of the Ottoman Empire we can perceive the disperse in morality and upheaval in the society in an exaggerated reflection to some degree. When folk stories and tales used create an artificial world of idealised characters against the difficulties of life, Folk Theatre/Orta Oyunu, Karagoz and Meddah/Eulogist stories were displaying the weaknesses and the defects of human behaviour and life in a generalized form. Folk stories and tales relates to an escape to a perfect dream world from the difficulties and ugliness of actual life. In opposition to that, there is a display of acceptance of the mistakes of the majority and the cruelty of life in Folk Theatre/Orta Oyunu, Karagoz, and Eulogist/Meddah stories. It is possible to observe the leap between the excess and the deficiency, which exists in the Turkish culture in these works. Bu makalede XV – XVI yüzyıllarda biçinlenmiş sözlü, şiirsel aşık yaratıcılığına XVIII yüzyıllarda İstanbul’da ortaya çıkmış meddah hikayelerinin klasik biçimiyle kıyas edinmiş. İncileme, hem metin konullarındaki hem de sanatsal imgelerindeki toplumsal ve ahlak değerlerin gösterilmesine göre yapılır.